Association Between Visceral Fat and Brain Cortical Thickness in the Elderly: A Neuroimaging Study - Cho, Jaelim; Seo, Seongho; Kim, Woo-Ram; Kim, Changsoo; Noh, Young (Frontiers in Aging Neuroscience, 2021)
Background: Despite emerging evidence suggesting that visceral fat may play a major role in obesity-induced neurodegeneration, little evidence exists on the association between visceral fat and brain cortical thickness in the elderly. Purpose: We aimed to examine the association between abdominal fat and brain cortical thickness in a Korean elderly population. Methods: This cross-sectional study included elderly individuals without dementia (n=316). Areas of visceral fat and subcutaneous fat (cm2) were estimated from computed tomography scans. Regional cortical thicknesses (mm) were obtained by analyzing brain magnetic resonance images. Given the inverted U-shaped relationship between visceral fat area and global cortical thickness (examined using a generalized additive model), visceral fat area was categorized into quintiles, with the middle quintile being the reference group. A generalized linear model was built to explore brain regions associated with visceral fat. The same approach was used for subcutaneous fat. Results: The mean (standard deviation) age was 67.6 (5.0) years. The highest quintile (versus the middle quintile) group of visceral fat area had reduced cortical thicknesses in the global (β=-0.04 mm, standard error [SE]=0.02 mm, p=0.004), parietal (β=-0.04 mm, SE=0.02 mm, p=0.01), temporal (β=-0.05 mm, SE=0.02 mm, p=0.002), cingulate (β=-0.06 mm, SE=0.02 mm, p=0.01), and insula lobes (β=-0.06 mm, SE=0.03 mm, p=0.02). None of the regional cortical thicknesses significantly differed between the highest and the middle quintile groups of subcutaneous fat area. Conclusions: The findings suggest that a high level of visceral fat, but not subcutaneous fat, is associated with a reduced cortical thickness in the elderly.